Post-protest continued blocks (Iran) - Voidly (2023)
CRITICAL severity censorship detected in Iran. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: IR-2023-0006
Keywords: censorship; IR; censorship; critical